Hubungan Pengetahuan Tentang Kanker Payudara dengan Perilaku SADARI pada Mahasiswi - Rudi Karmi; Yani Maryani; Indah Permata Sari (Ide Insan Kreatif, 2024)
Cancer is one of the biggest enemies of the Indonesian nation. This disease not only attacks men, but also women and at different ages. According to WHO data in 2018, especially teenagers who suffer from breast cancer reached 1,150,000 people, 700.000 are Indonesian. Information about risk factors for breast cancer and early breast screening is still not widely available in society, especially among women. Therefore, it is important for women to maintain breast health by carrying out early detection. Breast self-examination is a good way to prevent breast cancer, especially from the age of 20. The aim of this research was to determine the correlation between breast cancer knowledge and awareness behavior among female students at the Budi Luhur institute of Health Sciences. The method used is a cross-sectional analytical survey design. The sample in this research was 138 respondents. The results of the research showed that 83 respondents had less knowledge, 46 people (44.6%) had active behavior, out of 43 respondents had sufficient knowledge, 31 people (72.2%) had active behavior, out of 12 respondents had good knowledge, 8 people (66.7%) had active behavior. The conclusion there is a correlation between knowledge about breast cancer and Breast Self-examination behavior in female students at Budi Luhur of health sciences with a ρ-value of 0.009 < ɑ 0.05. So it is recommended that institutions should support Breast self-examination in order to find out as early as possible if there is a disorder or disease in the breast.Keywords: Knowledge, Behavior, and Breast self-examination